Composition operator induced by ?(z) = sz + t for which |s|?1, |t| (Baghdad Science Journal, 2025)
We study in this paper the composition operator that is induced by ?(z) = sz + t. We give a characterization of the adjoint of composiotion operators generated by self-maps of the unit ball of form ?(z) = sz + t for which |s|?1, |t|